Exploring Phytochemicals from Himalayan Medicinal Plants as Novel Therapeutic Agents - Saini, Nidhi; Lather, Viney; Gahlawat, Suresh K. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Over-prescription of medicines leads to some crucial health issues like resistance, non-specificity, etc. Therefore, a human consumes various natural foods, therapeutics, and nutritional supplements to combat this problem. Various therapeutic properties of secondary metabolites, such as anticancer, anti-inflammatory, and antibacterial properties, are important in drug discovery and medicinal application. These natural products have replaced synthetic materials, resulting in a great deal of sustainability, rational use, and preservation of biodiversity. This review described the potential therapeutic applications of secondary plant metabolites found in Himalayan Indian plants. The database contains 45 plants to treat various diseases, such as cancer, inflammation, and microbial infections. Besides authorized ITIS names, it includes Hindi names, family names, and active constituents. The most important information about the molecules can be found in the hyperlinks for the active constituents. It includes structures (two-dimensional and threedimensional), names and identifiers, chemical and physical properties, spectral information, biochemistry, literature and patents. The review also references various phytochemicals responsible for preventing COVID-19. Despite several challenges in manufacturing natural products, researchers may conduct research to produce successful medicines with few side effects.
Keywords: drug discovery